Extensive Superior Vena Caval Territory Thrombosis and Pulmonary Embolism: A Rare Clinical Entity of Haemorrhagic Pancreatitis - P. Thineskaran; K. Abiramy; T. Kumanan; V. Sujanitha; N. Suganthan; G. Selvaratnam (Case Reports in Gastrointestinal Medicine)
Acute haemorrhagic pancreatitis is a severe form of pancreatitis often encountered in ethanol abuse. Extensive venous thrombosis resulting in pulmonary embolism is a rare presenting clinical entity of acute haemorrhagic pancreatitis. Here, we report a young male with an extensive deep vein thrombosis involving superior vena caval territory associated with haemorrhagic pancreatitis presented with pulmonary embolism managed supportively. Prompt recognition and appropriate intervention of this rare complication would improve the outcome in patients with acute pancreatitis.